2011
DOI: 10.1186/1756-0500-4-129
|View full text |Cite
|
Sign up to set email alerts
|

Gut proteases target Yersinia invasin in vivo

Abstract: BackgroundYersinia enterocolitica is a common cause of food borne gastrointestinal disease. After oral uptake, yersiniae invade Peyer's patches of the distal ileum. This is accomplished by the binding of the Yersinia invasin to β1 integrins on the apical surface of M cells which overlie follicle associated lymphoid tissue. The gut represents a barrier that severely limits yersiniae from reaching deeper tissues such as Peyer's patches. We wondered if gut protease attack on invasion factors could contribute to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Inv and Ail proteins, and the pYV-encoded YadA. After penetration of the intestinal epithelium, yersiniae colonize the Peyer's patches and local lymphoid follicles, and may spread via the lymphatic system or the blood to other tissues, typically to mesenteric lymph nodes, spleen and liver where they form microabscesses (Trcek et al 2011). The ability to survive within these tissues is dependent on the presence of pYV.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Inv and Ail proteins, and the pYV-encoded YadA. After penetration of the intestinal epithelium, yersiniae colonize the Peyer's patches and local lymphoid follicles, and may spread via the lymphatic system or the blood to other tissues, typically to mesenteric lymph nodes, spleen and liver where they form microabscesses (Trcek et al 2011). The ability to survive within these tissues is dependent on the presence of pYV.…”
Section: Pathogenesismentioning
confidence: 99%
“…Chromosomally Encoded Virulence Factors Are also Needed Two chromosomal genes, inv and ail, are important for mammalian cell invasion (Trcek et al 2011). The inv gene codes for an outer-membrane invasion protein (Inv) which plays an important role in promoting the entry into epithelial M cells of the ileum during initial …”
Section: Virulencementioning
confidence: 99%
“…Thus, it is not surprising that mainly InvA has been used to test its use for bioinvasive drug carrier systems. Although gut proteases target invasin in vivo [78], it is possible to use smaller and more resistant protein fragments harboring only the invasive domain of…”
Section: Bacterial Invasins -Modular Factors Made For Host Cell Entrymentioning
confidence: 99%
“…Use of a longer 497-residue InvA fragment could be also beneficial for uptake, as it induces invasin self-association and  1 -integrins clustering which enhances uptake efficiency [74,88]. On the other hand, a larger InvA fragment might be more prone to degradation by intestinal proteases [78].…”
Section: Use Of Bacterial Invasion Factors For Drug Deliverymentioning
confidence: 99%
“…Unlike Y. Pestis, these two enteropathogens are commonly transmitted by food or water (Trcek et al, 2011). Multiple studies have indicated the involvement of Yops in the interaction of Yersinia and gut system.…”
Section: Interplay Of the Yersinia With Gut System And Tlrsmentioning
confidence: 99%